2011
DOI: 10.3109/02770903.2011.627487
|View full text |Cite
|
Sign up to set email alerts
|

Fractional Exhaled Nitric Oxide in Relation to Asthma, Allergic Rhinitis, and Atopic Dermatitis in Chinese Children

Abstract: Both asthma and AR could independently increase the FeNO levels in Chinese schoolchildren. Other diseases besides asthma should be considered when applying FeNO as a screening tool for asthma in Chinese children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 28 publications
5
11
0
Order By: Relevance
“…We found only one study on SBS symptoms among office workers and FeNO levels and this study found no association between nasal symptoms and FeNO levels (Akpinar-Elci et al, 2008). However, two recent epidemiological studies among school children in China demonstrated that rhinitis is more common at higher FeNO levels (Xu et al, 2011;Zhao et al, 2013).…”
Section: Discussionmentioning
confidence: 91%
“…We found only one study on SBS symptoms among office workers and FeNO levels and this study found no association between nasal symptoms and FeNO levels (Akpinar-Elci et al, 2008). However, two recent epidemiological studies among school children in China demonstrated that rhinitis is more common at higher FeNO levels (Xu et al, 2011;Zhao et al, 2013).…”
Section: Discussionmentioning
confidence: 91%
“…Fractional exhaled nitric oxide (FeNO) is a well-established airway inflammatory biomarker employed in both clinical practice and epidemiological studies due to its high reproducible and noninvasive nature (Adamkiewicz et al, 2004;American Thoracic and European Respiratory, 2005;Dales et al, 2008;Dweik et al, 2011;Liu et al, 2009). A wide array of epidemiological studies has demonstrated a significant link between a short-term exposure to PM 2.5 and elevated FeNO levels (Chen et al, 2015b;Xu et al, 2011;Zhao et al, 2013). PM 2.5 is composed of a vast number of chemical constituents.…”
Section: Introductionmentioning
confidence: 99%
“…Fraction of exhaled nitric oxide (FeNO) has recently been used in epidemiological studies in Asia (Xu et al, 2011;Zhao et al, 2013;Lim et al, 2015). FeNO is a biomarker of TH2 driven lower airway inflammation linked to allergic asthma (Alving and Malinovschi, 2010) rhinitis (Xu et al, 2011, Zhao et al, 2013Lim et al, 2015a) and sick building syndrome (SBS) symptoms (Lim et al, 2015b).…”
Section: Introductionmentioning
confidence: 99%
“…FeNO is a biomarker of TH2 driven lower airway inflammation linked to allergic asthma (Alving and Malinovschi, 2010) rhinitis (Xu et al, 2011, Zhao et al, 2013Lim et al, 2015a) and sick building syndrome (SBS) symptoms (Lim et al, 2015b). FeNO has been measured among office workers in Malaysia (Lim et al, 2015, Lim et al, 2016 but we found no previous publications from Malaysia, or any other tropical country, on associations between FeNO and the school environment.…”
Section: Introductionmentioning
confidence: 99%